Take time to look at the fish: Behavioral response to acute thermal challenge in two Amazonian cichlids. Issue 9 (7th September 2021) - Kochhann, Daiani; Sarmento, Carolina G.; de Oliveira, Jomara C.; Queiroz, Helder L.; Val, Adalberto L.; Chapman, Lauren J.
Abstract: Critical thermal maximum (CTmax ) is often used as an index of upper thermal tolerance in fishes; however, recent studies have shown that some fishes exhibit agitation or avoidance behavior well before the CTmax is reached. In this study, we quantified behavioral changes during CTmax trials in two Amazonian cichlids, Apistogramma agassizii and Mesonauta insignis . The thermal agitation temperature ( T ag ) was recorded as the temperature at which fish left cover and began swimming in an agitated manner, and four behaviors (duration of sheltering, digging, activity, and aquatic surface respiration [ASR]) were compared before and after T ag . Both A. agassizii and M. insignis exhibited high critical thermal maxima, 40.8°C and 41.3°C, respectively. Agitation temperature was higher in M. insignis (37.3°C) than in A. agassizii (35.4°C), indicating that A. agassizii has a lower temperature threshold at which avoidance behavior is initiated. Activity level increased and shelter use decreased with increased temperatures, and patterns were similar between the two species. Digging behavior increased after T ag in both species, but was higher in A. agassazii and may reflect its substrate‐oriented ecology. ASR (ventilating water at the surface film) was extremely rare before T ag, but increased in both cichlid species after T ag and was greater in M. insignis than in A. agassizii . This suggests that fish were experiencing physiological hypoxia at water temperatures approaching CTmax . These results demonstrate that acute thermal challenge can induce a suite of behavioral changes in fishes that may provide additional, ecologically relevant information on thermal tolerance. Abstract : Critical thermal maximum (CTmax ) is often used as an index of upper thermal tolerance in fishes; however, recent studies have shown that some fishes exhibit agitation or avoidance behavior well before the CTmax is reached. Two Amazonian cichlids Apistogramma agassizii and Mesonauta insignis exhibited high critical thermal maxima, 40.8°C and 41.3°C, respectively. However, the agitation temperature was higher in M. insignis (37.3°C) than in A. agassizii (35.4°C), indicating that A. agassizii has a lower temperature threshold at which avoidance behavior is initiated. Highlights: Two Amazonian cichlid species increased activity, digging, and aquatic surface respiration in response to acute thermal challenge. The first signs of behavioral agitation occurred well before fish reached their upper thermal limit (CTmax ).